Alfabetização científica: compreensões dos professores de ciências da rede municipal de Cascavel-PR - Aguera, Josiane dos Santos (2024)
Most teachers who teach science to elementary school students in the municipal school system of Cascavel, Paraná, do not have specific training in natural sciences. In fact, the majority hold only a degree in pedagogy. These teachers, referred to as “Regentes II”, are responsible for teaching the curricular components of science, arts, and physical education. With this in mind, we found from this research that the teachers we interviewed, for the most part, have doubts or insecurities regarding specific aspects of natural sciences in elementary school level (Ensino Fundamental I). Thus, this study sought to identify comprehensions about the scientific literacy of teachers in the municipal school system of Cascavel, Paraná. To this end, we conducted qualitative research involving semi-structured interviews with 15 teachers working as Regentes II in municipal schools during 2023. These 15 participants work in different regions of the municipality, which we consider relevant to have a broad perspective on our research topic. Data analysis was performed using content analysis, through which we developed a posteriori categories addressing the concepts of scientific literacy and the pedagogical practices of teachers working with the science curricular component. The research revealed that, among the participants, the vast majority of teachers are unfamiliar with the concept of scientific literacy, primarily due to their initial teacher education, which was exclusively in pedagogy.